Muscular strength and jumping performance relationships in young women athletes - Rousanoglou, E. N.; Georgiadis, G. V.; Boudolos, K. D. (The Journal of Strength and Conditioning Research, 2008)
The relationships between muscular strength and vertical jumping performance were examined in young women (14-19 years) track and field jumpers (n = 20) and volleyball players (n = 21). The knee extensor muscular strength measured at 9 knee angles was correlated with jumping height and peak power at the squat (SJ) and the countermovement (CMJ) vertical jump tests. Pearson product coefficient of correlation was used to test the significance of these relationships (p <= 0.05). The relationships were strong to moderate, but only in the volleyball players (p <= 0.05 and power of analysis >0.80). Specifically, in the volleyball players, the strong relationships were noted for muscular strength at the knee angle range of 40° to 90° and CMJ jumping height as well as SJ peak power. Results indicate the dissimilarity in the relationships between the knee extensor muscular strength and jumping performance in the young female track and field jumpers and volleyball players. In addition, it appears that the measure selected to evaluate jumping performance alters the correlational results.